2021
DOI: 10.1002/advs.202102785
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Oropharyngeal Microbiomes in SARS‐CoV‐2 Infection and Recovery Patients

Abstract: Respiratory tract microbiome is closely related to respiratory tract infections, while characterization of oropharyngeal microbiome in recovered coronavirus disease 2019 (COVID-19) patients is not studied. Herein, oropharyngeal swabs are collected from confirmed cases (CCs) with COVID-19 (73 subjects), suspected cases (SCs) (36), confirmed cases who recovered (21), suspected cases who recovered (36), and healthy controls (Hs) (140) and then completed MiSeq sequencing. Oropharyngeal microbial 𝜶-diversity is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 48 publications
2
46
2
1
Order By: Relevance
“…However, the oral microbiota of mild COVID-19 patients in our research showed coherent decreased richness (Chao1 index, not significant) but increased Shannon biodiversity compared to the HCs, which showed inconformity to previous research (Iebba et al, 2021;Ma et al, 2021). Nonetheless, when we divided SARS-CoV-2 patients into two groups with higher and lower viral burdens, interestingly, a significantly increased trend of alpha richness (Chao1 index) and Shannon biodiversity, although not significant, was found in those patients with higher SARS-CoV-2 viral load, which was inconsistent with previous studies (Gao et al, 2021;Ma et al, 2021;Wu et al, 2021). These results indicated dysbiosis in the oropharyngeal bacteria of patients infected with SARS-CoV-2.…”
Section: Discussioncontrasting
confidence: 98%
“…However, the oral microbiota of mild COVID-19 patients in our research showed coherent decreased richness (Chao1 index, not significant) but increased Shannon biodiversity compared to the HCs, which showed inconformity to previous research (Iebba et al, 2021;Ma et al, 2021). Nonetheless, when we divided SARS-CoV-2 patients into two groups with higher and lower viral burdens, interestingly, a significantly increased trend of alpha richness (Chao1 index) and Shannon biodiversity, although not significant, was found in those patients with higher SARS-CoV-2 viral load, which was inconsistent with previous studies (Gao et al, 2021;Ma et al, 2021;Wu et al, 2021). These results indicated dysbiosis in the oropharyngeal bacteria of patients infected with SARS-CoV-2.…”
Section: Discussioncontrasting
confidence: 98%
“…The composition of the nasal microbiome has been observed to be altered in several respiratory infections including COVID-19 affecting the course of the disease and clinical outcome ( 44 ). Different metagenomic studies portrayed decrease in the nasopharyngeal microbiome diversity in SARS-CoV-2 infected patients, leading to predominance of a specific microbe that correlated with symptom severity ( 22 , 23 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, co-infections deserve closer attention to understand and evaluate their role in disease management and patient outcome ( 21 ). Few studies have illustrated the function of respiratory microbiome in SARS-CoV-2 infection, emphasizing the role of co-infecting pathogens as prospective modulators of COVID-19 ( 22 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other opportunistic pathogenesis of the upper respiratory tract like Haemophilus, Stenotrophomonas, Acinetobacter, Moraxella, Corynebacterium, Gemella, Ralstonia, Pseudomonas [53], Granulicatella [52], Megasphaera [25] were increased in COVID-19 patients which are associated with serious clinical outcomes. Also, in Severe COVID-19 patients, an increase of Megasphaera, and infatal COVID-19 patients increase Rothiadentocariosa, Streptococcus infantis, Veillonelladispar [21] were seen which may be associated with secondary pneumonia due to mechanical ventilation.…”
Section: Upper Respiratory Tract Microbiotamentioning
confidence: 98%